Enterprise resource planning systems for the textiles industry: a study on Square Textiles Limited. - Hossain, S.M. Saroare (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.